Perancangan Website Presensi Berbasis QR Code untuk Kegiatan Anak Misioner di Gereja Santo Antonius Padua dengan Metode Waterfall - Ananda andreas dharma shadana; Agung Nugroho (Program Studi Teknik Informatika Universitas Pamulang, 2025)
The Missionary Children activity at Santo Antonius Padua Church is a strategic program for early childhood spiritual education. However, the administrative management, specifically student attendance recording, still relies on a manual system using paper forms. This conventional method is deemed highly inefficient due to the time-consuming roll-call process, high susceptibility to human errors in data entry, and the lack of real-time data transparency for parents, who can currently only access attendance records at the end of the program. To overcome these significant administrative limitations, this research aims to design and build a comprehensive web-based attendance information system utilizing Quick Response (QR) Code technology. The system development process strictly adopts the systematic flow of the Waterfall model, covering requirements analysis, system design, coding, testing, and maintenance. Technically, the system is developed using the PHP programming language with the Laravel framework, coupled with PostgreSQL as a reliable database management system. It accommodates distinct user roles Management, Mentors, and Parents offering specific functionalities such as session management and child ID card generation. Functionality validation was conducted using the Black Box Testing method. The results confirm that the website functions optimally, enabling rapid attendance recording through QR code scanning using external scanners. Consequently, this system serves as a viable solution for enhancing administrative efficiency, minimizing data manipulation, and providing parents with immediate access to their children's attendance history.